Analisis terhadap Sanksi Korporasi Pelaku Dumping Limbah tanpa Izin Perspektif HAM - Ibrohim, Ali; Budiarsih, Budiarsih; Suhartono, Slamet (Tapis: Jurnal Penelitian Ilmiah, 2020)
Law Number 23, 2009 concerning Environmental and Management Protection has been running for eleven years. This law still needs a lot of evaluation, especially at the level of implementation or implementation. One of them is related to the sanction for corporations that do environmental damage. There are three types of sanctions that can be given to corporations, namely: civil, criminal and administrative. However, all this time the three did not provide a deterrent effect. As a result, the rights of affected citizens to get a healthy environment are also ignored. For this reason, this paper focused on how is the Analysis of corporate sanctions of perpetrators of waste dumping without permission viewed from a Human Rights perspective? This study uses a juridical normative research method, by analyzing secondary data in the form of laws and regulations related to sanctions for corporations that carry out waste dumping without permission. The results of the study found that the analysis of corporate sanctions for the perpetrators of waste dumping without permission did not represent the protection of human rights for the community. Legal fissures make the corporation can continue its activities and make it possible to do environmental damage again. It is necessary to maximize the application of the highest alternative sanctions by paying attention to human and community rights around the location of waste dumping where the quality of water, air, and soil has deteriorated.